Empowerment Assistance for Routine Tahsin Al-Qur'an Activities Using the An-Nahdliyah Method - Arsyad, Mufid; Ahmad Mahluqi; Adnan Maulana; Ferdi Yogi Saputra; Rizki Ragil; Sumiyati Dewi; Vina Anggraini (Jurnal Insan Pengabdian Indonesia, 2024)
Community service through Social Work Lectures (KKS) is one form of student contribution in overcoming problems in society. This research aims to examine the role of KKS in increasing public awareness and providing education to the community in Trimorjo Village, Metro. The method used in this research is observation. KKS students participated in activities to create public awareness of the importance of science, to create quality, character, creative and innovative human resources. The research results show that through KKS, public awareness in Trimorjo Metro Subdistrict has increased significantly. The public is starting to understand how important it is to learn to deepen Islamic knowledge, especially in the field of reading the Al-Qur'an properly and correctly, also showing increased knowledge about the importance of learning to read the Al-Quran using methods that have been socialized through educational activities carried out by female students. KKS to the Trimurjo community.